The Principal Strategy For Creating Organizational Culture in Bojonegoro District - Sahri; Kojin; Munardji (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to determine the principal’s strategy for building an organizational culture in educational institutions. Because the principal has an important role in building an organizational culture to create a safe and pleasant atmosphere in learning, the type of research used is qualitative research. This research was conducted at Bojonegoro Regency. Sources of data taken are principals, teachers, and good students in collecting data using in-depth interviews, observation, and documentation. Furthermore, in analyzing the data using data collection, data condensation, and conclusion. There are several organizational cultures developed by the principal, namely through religious culture, achievement culture, clean environment culture, discipline culture, and reading culture.